2000
DOI: 10.1590/s0102-05362000000300010
|View full text |Cite
|
Sign up to set email alerts
|

Shoot tip culture and thermotherapy for recovering virus-free plants of garlic

Abstract: Garlic shoot tip culture associated with dry heat thermotherapy (cloves exposed to 37°C for 35 days) were essential for recovering virus free plants of the cv Amarante. In this condition 70% of the explants developed in vitro and produced plants. A total of 77% of those plants was virus free when indexed by ISEM, which resulted in a final index of 54% of virus free plants from treated cloves. The percentage of regeneration decreased to 20% as the temperature increased up to 40°C. However 90% of those plants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
0
13
0
4
Order By: Relevance
“…Garlic shoot tip culture associated with dry heat treatment (cloves exposed to 37°C for 35 days) were essential for recovering virus-free plants of the Amarante cultivar. In this condition, 70% of the explants developed in vitro and produced plants (Torres et al, 2000). Meristem culture of potato using explants 100 μm in length combined with thermotherapy at approximately 37±1°C for 40 days produced a high rate of virus-free plants, 81% in the Binella cultivar and 75% in the Burren cultivar (Almaarii et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…Garlic shoot tip culture associated with dry heat treatment (cloves exposed to 37°C for 35 days) were essential for recovering virus-free plants of the Amarante cultivar. In this condition, 70% of the explants developed in vitro and produced plants (Torres et al, 2000). Meristem culture of potato using explants 100 μm in length combined with thermotherapy at approximately 37±1°C for 40 days produced a high rate of virus-free plants, 81% in the Binella cultivar and 75% in the Burren cultivar (Almaarii et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…Meristem tissues that had undergone thermotherapy resulted in regeneration of fewer plants than the nontreated meristems, but 90 to 100% plants from thermotherapy treated meristem tissues were found to be free from OYDV. Torres et al, (2000) recovered 90% plants free of virus from the cloves of garlic cultivar Amarante through dry heat thermotherapy (37 °C for 35 days). However, according to Ramirez et al, (2006) though mericlones produced through thermotherapy were found to be free from viruses, but the overall efficiency of virus elimination was low.…”
Section: Thermotherapymentioning
confidence: 99%
“…Jenis virus tertentu juga sulit dieliminasi sehingga memerlukan kombinasi perlakuan tertentu (Wang & Valkonen 2012). Torres et al (2000) melaporkan bahwa perlakuan termoterapi atau kultur meristem yang diaplikasikan secara tunggal tidak dapat mengeliminasi virus pada bawang putih, namun ketika kedua perlakuan tersebut dikombinasikan maka eliminasi virus dapat terjadi. Eliminasi virus juga terjadi pada kentang yang diberi kombinasi perlakuan termoterapi dan kultur meristem (Ali et al 2013).…”
Section: Pendahuluanunclassified